Una heroica dama? The Discurso en loor de la poesía (1608) in context and the case for Diego Mexía as 'Clarinda'. - Feile Tomes, Maya (Colonial Latin American Review, 2023)
This article re-visits the matter of the much debated identity of the author of the Discurso en loor de la poesía (1608). Inspired by the anonymous writer's introduction as an heroica dama and señora principal de este reino, it is generally accepted that the Discurso is the work of an eminent Peruvian woman who has entered scholarly tradition under the pseudonym 'Clarinda.' The article suggests that there are grounds, both methodological and literary, to contest this identification. Instead, it seeks to reinscribe the Discurso en loor de la poesía into the context of the volume in which it originally appeared—Diego Mexía de Fernangil's Primera parte del Parnaso Antártico—and to interpret it as part of Mexía's broader literary project, which is an Ovidian one. Reassessing the Discurso through the lens of Ovid—more specifically, his Heroides—permits a new Heroidean reading which ultimately intuits Mexía himself behind the pen. The article further contends that the Discurso's formal status as a work of poetics corroborates this interpretation. What emerges is not a diminishment of the work of the so-called señora but rather an amplification of the poem's dynamic potential, setting the stage for future work on this rich but misunderstood text.